Fatwa and Religious Authority: Islamic Law, Social Media Ethics and Digital Age - Abdurrohman Kasdi; Umma Farida; Miftahul Huda; Akmal Fawwaz Aulia Rahman; Ahmad Dakhoir (Faculty of Sharia, Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Fatwas issued by the ulama play a strategic role in shaping the trajectory of Muslim thought in the digital era, particularly as many Muslims lack direct access to, or the capacity to independently interpret, the primary sources of Islamic law such as the Qur’an and Hadith. This study examines the position of fatwas as a determinant of religious authority and explores their implications for the development of Islamic law in the digital age. Employing a qualitative research design, this study analyzes fatwas issued by the Indonesian Ulama Council (Majelis Ulama Indonesia/MUI) concerning socio-religious issues. Data were collected through library research and examined using a normative-analytical approach, emphasizing contextual interpretation and doctrinal analysis. The findings demonstrate that MUI fatwas occupy a position of significant religious authority within the construction of Islamic law and possess substantial sociological and moral binding force. Muslim communities adhere to these fatwas because they are perceived as authoritative interpretations grounded in Islamic legal principles. Furthermore, fatwas contribute to the dynamic development of Islamic law and influence national legal frameworks. In the digital era, religious authority has become increasingly strategic, particularly following the issuance of MUI Fatwa No. 24 of 2017, which provides ethical guidelines for social media engagement, promotes social harmony, and seeks to prevent societal fragmentation in Indonesia.